Proceedings of the 48th International Symposium on Microarchitecture 2015
DOI: 10.1145/2830772.2830779
|View full text |Cite
|
Sign up to set email alerts
|

TimeTrader

Abstract: Online Search (OLS) is a key component of many popular Internet services. Datacenters running OLS consume significant amounts of energy. However, reducing their energy is challenging due to their tight response time requirements. A key aspect of OLS is that each user query goes to all or many of the nodes in the cluster, so that the overall time budget is dictated by the tail of the replies' latency distribution; replies see latency variations both in the network and compute. Previous work proposes to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Paragon 9 and Quasar 10 predict and detect the resource interference between jobs through workload profiling and application classification, and select the optimal node accordingly. In addition, there were studies that supported granular partitioning to analyze and eliminate the cases of interference between latency‐sensitive jobs and best‐effort batch jobs when deploying the application to the node 11‐16 . These studies focused on resource guarantee and efficient idle resource consumption.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Paragon 9 and Quasar 10 predict and detect the resource interference between jobs through workload profiling and application classification, and select the optimal node accordingly. In addition, there were studies that supported granular partitioning to analyze and eliminate the cases of interference between latency‐sensitive jobs and best‐effort batch jobs when deploying the application to the node 11‐16 . These studies focused on resource guarantee and efficient idle resource consumption.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, there were studies that supported granular partitioning to analyze and eliminate the cases of interference between latency-sensitive jobs and best-effort batch jobs when deploying the application to the node. [11][12][13][14][15][16] These studies focused on resource guarantee and efficient idle resource consumption. On the other hand, detailed control of the resources used by best-effort batch jobs with a low priority was not studied thoroughly.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent works [24,40,60,[161][162][163] have shown that traditional power management practices and CPU utilisation measures are unsuitable to drive task management for data centre workloads. This is because prior schemes (like OS-level DVFS) work well to deliver long-term performance for batch workloads, but they can severely hurt the QoS of latency-critical data centre workloads.…”
Section: Maurice Herzogmentioning
confidence: 99%